Greenhouse Effect Education Against Climate Change Through an Accelerometer-Based Android Game - Mahendra Jordan; FX Hendra Prasetya; Bernadinus Harnadi (Soegijapranata Catholic University, 2022)
Climate change has become a global issue, the greenhouse effect is the main cause of climate change. The greenhouse effect has an important role in keeping the earth's temperature warm. But greenhouse gases are increasing which is why global average temperatures continue to rise. These greenhouse gas emissions are caused by humans, such as the use of fossil fuels as an energy source, excess methane from livestock and burning forests as CO2 absorbers. For this reason, how humans reduce greenhouse gas emissions such as switching from fossil materials to alternative energy, using public transportation rather than private vehicles, reducing meat consumption and so on. Education through games will learn all of this in different ways, using the accelerometer as the main control is a challenge for playersThis paper has purpose how to arrange the greenhouse effect material in the form of an Android-based game. Game testing data through submitting several statements to respondents. Questionnaires were distributed to respondents who had directly played this game. After testing the game, it is found that the convenience variable and the pleasure variable have a correlation with the desire to return to use.